Impact of Demographic Dividend on Economic Growth: A Study of BRICS and the EU. (January 2015) - Misra, Roli
As the countries pass through the different stages of demographic transition in their process of development, a window of a demographic opportunity opens in the phase of rapidly declining infant mortality. The result is an increase in the share of young adults in the population leading to a 'youth bulge'. This bulge is indicative of a large share of the working ages in the population which yield a demographic dividend and a low dependency ratio. The dividend, however, is transient. The lower fertility will eventually reduce the growth rate of this potential labour force along with mortality speeding the growth of elderly population. Thus, countries need to ensure timely implementation of effective policies to realize the dividend. In this background, this article attempts to study how economic growth of any country gets influenced by its demographic dividend. In this study, we have selected Brazil, Russia, India, China and South Africa (BRICS) and the European Union to see this relationship between two variables economic growth and demographic dividend using fixed effect model covering a period of 1990–2015. The results from regression equation exhibit that relationship between GDP growth rate and demographic dividend is positive thus, validating our hypothesis that demographic dividend has a positive impact on economic growth.